V-037 PARASTOMAL MESH INFECTIONS WITH INTESTINAL FISTULA: 2 RARE SURGICAL CASES AND HOW WE FIXED THEM. (13th October 2022) - Bertoglio, C L; Quagli, O; Grimaldi, S; Alampi, B; Morini, L; Ferrari, G
Abstract: Parastomal hernias (PSH) occur in 50–80% after stoma formation and its treatment is considered a real challenge. According to the recent literature, the use of prophylactic mesh at the time of primary stoma should decrease the odds of hernia formation. The most common occurrences after PSH surgery are: recurrence, seroma and wound complications. In this video, we report 2 cases of mesh infection with fistula necessitated removal after 10 and 4 years of mesh placement. The first patient was a 66 years-old male. In 2007 he underwent radical prostatectomy and pelvic lymphadenectomy following radiotherapy. He underwent a radical cystectomy and Bricker's cutaneous uretero-ileostomy for stenosis of the vesicourethral anastomosis. In 2012 for PSH he underwent laparo-alloplasty with a placement of an intraperitoneal mesh. In February 2022, with fever and dyspnoea, at the CT-scan of the abdomen we found air bubbles near the mesh and a suspected sigmoid-to-mesh fistula. The second patient was a 66 years old male. In 2018 the patient underwent neoadjuvant radiotherapy, then Miles' procedure and prophylactic 3D intraperitoneal mesh, subsequent adjuvant therapy. During the oncological follow-up an abdominal CT-scan showed air bubbles around the stoma and suspicion of fistula on the adjacent intestinal loops. In both cases there was an infection of the area around the stoma due to a fistula between the mesh and the intestine. We proceeded, in laparoscopy, to remove the infected mesh. We converted in open surgery with the resection of the fistulized intestine tract and we did a new ostomy.